Analysis of Fraud Prevention Actions by Banking Employees - Anggraini, Veni; Rosidi; Lisa, Oyong (International Journal of Economics and Business Management, 2024)
Fraud is a form of fraud committed by banking officials to gain illegal profits from banks or customers. This study aims to test fraud prevention measures in the banking sector through organizational culture variables, internal auditors, whistleblowing and internal control systems. The internal control system in this study acts as an intervening variable. We use the size of rural bank employees in Kediri City to test the causal relationship on the research variables through statistical data analysis. The results of the study indicate that organizational culture, whistleblowing and internal control systems have a significant effect on fraud prevention in rural bank services. On the other hand, the role of internal auditors does not affect fraud prevention measures. Organizational culture and the role of internal auditors have a significant effect on fraud prevention through the implementation of internal control systems and whistleblowing has a significant effect on fraud prevention through the implementation of internal control systems. The findings of this study are expected to help stakeholders in efforts to prevent fraud in the banking sector